Antitumor activity and other biological actions of oligomers of ribonuclease A - Matousek, Josef; Gotte, Giovanni; Pouckova, Pavla; Soucek, Josef; Slavik, Tomas; Vottariello, Francesca; Libonati, Massimo (The Journal of biological chemistry, 2003)
Dimers, trimers, and tetramers of bovine ribonuclease A, obtained by lyophilization of the enzyme from 40% acetic acid solutions, were purified and isolated by cation exchange chromatography. The two conformers constituting each aggregated species were assayed for their antitumor, aspermatogenic, or embryotoxic activities in comparison with monomeric RNase A and bovine seminal RNase, which is dimeric in nature. The antitumor action was tested in vitro on ML-2 (human myeloid leukemia) and HL-60 (human myeloid cell line) cells and in vivo on the growth of human non-pigmented melanoma (line UB900518) transplanted subcutaneously in nude mice. RNase A oligomers display a definite antitumor activity that increases as a function of the size of the oligomers. On ML-2 and HL-60 cells, dimers and trimers generally show a lower activity than bovine seminal RNase; the activity of tetramers, instead, is similar to or higher than that of the seminal enzyme. The growth of human melanoma in nude mice is inhibited by RNase A oligomers in the order dimers < trimers < tetramers. The action of the two tetramers is very strong, blocking almost completely the growth of melanoma. RNase A dimers, trimers, and tetramers display aspermatogenic effects similar to those of bovine seminal RNase, but, contrarily, they do not show any embryotoxic activity.
Keywords: myši; nádorové buňky kultivované; dimerizace; Ribonuclease, Pancreatic; lidé; Melanoma; Humans; buněčné dělení; peptidové fragmenty; Mice; Animals; Spermatogenesis; Peptide Fragments; protinádorové látky; Antineoplastic Agents; Protein Conformation; zvířata; melanom; Cattle; Cell Division; skot; konformace proteinů; Transplantation, Heterologous; Embryo, Mammalian; spermatogeneze; ženské pohlaví; Tumor Cells, Cultured; Female; embryo savčí; vztahy mezi strukturou a aktivitou; pankreatická ribonukleasa; Dimerization; transplantace heterologní; Structure-Activity Relationship